Phalloplasty – Sensate radial forearm free flap for creation of neourethra and neophallus in gender affirmation surgery: A case report - Taliat, George; Mohan Kumar, Kumaraswamy; Nagaraj, Arjun (Journal of Surgery and Medicine, 2021)
With an increase in gender affirmation surgery requirements, it is imperative to understand the procedure for phalloplasty. The Radial Forearm Free Flap is one of the most commonly used flaps for the same. We present this case of a 29-year-old patient who underwent phalloplasty by means of a radial artery forearm free flap. Surgical technique has been described including flap design, harvest, recipient site preparation, anastomosis of vessels and nerves, and post-operative care. The patient developed a small area of partial necrosis which was the dorsoulnar border of the flap. The rest of the neophallus and neourethra were viable, sensate and the patient was able to void urine through the neourethra while standing. The radial forearm free flap is a good option for phalloplasty in gender affirmation surgeries. However, surgeons need to be wary of the possibility of necrosis of the dorsoulnar aspect which may be exceeding the radial artery territory.